LEGAL PROTECTION FOR MEMBERS OF THE MARTIAL ARTS PENCAK SILAT - Hanin Alya’ Labibah; Arum Ayu Lestari (Faculty of Law Universitas 17 Agustus 1945 Semarang, 2022)
Pencak silat is an art both with bare hands and weapons used to defend yourself, one of the agendas of which is fighting, namely mechanical fighting one-onone or more so that it is inevitable that there will be things that cause injuries caused by punches or kicks. The purpose of this study is to find out the legal certainty regarding injuries that occur during martial arts training, become a polemic of how the law views it and how it is protected, the existence of conflicting regulations and theories are things that must be considered so that there are no harmful regulations for one of the parties. This paper uses normative legal research with conceptual approach methods and statutory approaches. The result of this study is that injuries due to violence are criminal acts that have been regulated in the Criminal Code. However, on the grounds that the criminal removal of the criminal act is not a criminal act.